Factors influencing teamwork among employees of Jabatan Perdana Menteri at Putrajaya / Mohamad Hakam Atiq Hamzah - Hamzah, Mohamad Hakam Atiq (Faculty of Business and Management, 2019)
This study is conducted to measure Factors influencing teamwork among employees of Jabatan Perdana Menteri at Putrajaya. Emphasizing the respondent’s from similar background industry. The teamwork elements are form under three main dimensions, mainly is coordination, communication and mutual support. Meanwhile, the dependent variable to be measured under this concept is employees’ teamwork. The researcher has adopted the descriptive research on the issue. Then, the researcher’s sampling design is non-probability sampling which is convenience sampling method with 200 questionnaires were distributed to employees within the given time period. Data were collected and evidences are being processed by using Statistical Package for Social Science (SPSS) program. The findings analysis includes descriptive analysis, reliability testing, correlation and multiple regression analysis. The outcome of multiple regression analysis showed that communication, and mutual have positive significant impact on employees’ teamwork except coordination. In conclusion, its how’s that the organization which provides good teamwork elements to the employees will ultimately enhance their satisfaction and improve organizational performance.